Manipulação de spin em diodos de tunelamento ressonante não-magnéticos tipo-n - Santos, Lara Fernandes dos (2010)
The aim of this work was to study the spin effects in non-magnetic asymmetric n-type resonant tunneling diodes (RTD). For this purpose, we have used transport and polarization resolved magneto-photoluminescence measurement techniques. The optical polarization degree from quantum well (QW) and contact layers regions was studied as a function of voltage bias and magnetic field . In general, we have observed that the optical polarization and the excitonic spin-splitting from the QW emission is sensitive to the voltage bias. The contact layers emission as a funcition of voltage bias was also investigated under fixed magnetic field and it has shown large degrees of negative circular polarization. This behavior was associated to the occupation of the spin-split valence band in the GaAs bulk. We have also observed that the bi-dimensional electron gas (2DEG) emission is magnetic field favored by the magnetic field, as it has been reported in the literature. However, this study revealed that this emission also can be voltage bias induced. In addition, we unexpectly observed that the 2DEG-H and the 3D bulk emissions can exhibit up to -100% and +90 % of optical polarization degree respectively, depending on the voltage conditions. Emissions from the QW and contact layers were also investigated as a function of the magnetic field. We have observed that the polarization from QW and the 2DEG-H have an oscillatory behavior at some integer filling factor. Our results show that the circular polarization of the carriers in the QW should depend on various mechanisms, including the Landè g-factors of the different layers and the spin-polarization of the carriers in the contact layers and the density of carriers along the structure.